Physicochemical Properties of Water Courses in Tatra National Park - Gura, Ondrej; Graban, Jan; Maximova, Natalia; Greguskova, Eva (Communications - Scientific letters of the University of Zilina, 2013)
The aim of this study is to present an informative overview of the physicochemical properties of a representative sample of water courses located within Tatra National Park. The water quality of 28 selected water courses was monitored at altitudes from 639 to 2002 m a.s.l. Water temperature, pH, conductivity, concentrations of total dissolved solids, salinity and dissolved oxygen were measured from June to October 2010. The concentration of dissolved oxygen ranged from 5.90 to 16.46 mg/l, conductivity ranged from 5.30 to 282.60 μS/cm and pH averaged 7.25. An inverse relationship was found between nitrate and altitude as well as between conductivity and altitude. Measurements were consistent with the rating for very pure water. The results obtained serve as initial findings and form the basis for further biotic monitoring of water quality in the Tatra Mountains.